The fiscal effects of aid in Ghana - Robert Osei; Oliver Morrissey; Tim Lloyd (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
An important feature of aid to developing countries is that it is given to the government. As a result, aid should be expected to affect fiscal behaviour, although theory and existing evidence is ambiguous regarding the nature of these effects. This paper applies techniques developed in the `macroeconometrics' literature to estimate the dynamic linkages between aid and fiscal aggregates. Vector autoregressive methods are applied to 34 years of annual data in Ghana to model the effect of aid on fiscal behaviour. Results suggest that aid to Ghana has been associated with reduced domestic borrowing and increased tax effort, combining to increase public spending. This constructive use of aid to maintain fiscal balance is evident since the mid-1980s, following Ghana's structural adjustment programme. The paper provides evidence that aid has been associated with improved fiscal performance in Ghana, implying that the aid has been used sensibly (at least in fiscal terms). – aid ; fungibility ; fiscal response ; impulse response
Keywords: F35; O23; O55; H60; 330; Entwicklungshilfe; Öffentliche Finanzwirtschaft; Ghana